Economic Viability Solar PV Power Plant in Distribution System. (August 2019) - Pujan Jaiswal, Shiva; Shrivastava, Vivek; Singh, Shashank
Abstract: Silicon is definitely, the most common substance used for manufacturing solar cells. Distributed Generation (DG) based on Solar Photo Voltaic (PV) cells enhance the voltage stability and economical profit as well as reduce the carbon emission. This manuscript optimized the location and size of PV base DG for the 13-Bus distribution network, using the nature base Particle Swarm Optimization (PSO) algorithm. This manuscript also gives an overview of the process of manufacturing of PV cell. The core intention of this manuscript is to demonstrate the economical benefits of optimal PV based generation unit. Results prove that the PV base power plant improves the technical performance as well as economical performance of the system.